2021
DOI: 10.2337/dc20-2878
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Open-Label Comparison of Once-Weekly Insulin Icodec Titration Strategies Versus Once-Daily Insulin Glargine U100

Abstract: Insulin icodec is a novel once-weekly basal insulin analog. This trial investigated the efficacy and safety of icodec using different once-weekly titration algorithms. RESEARCH DESIGN AND METHODSThis was a phase 2, randomized, open-label, 16-week, treat-to-target study. Insulin-naïve adults (n 5 205) with type 2 diabetes and HbA 1c 7-10% while treated with oral glucose-lowering medications initiated once-weekly icodec titrations A (prebreakfast self-measured blood glucose target 80-130 mg/dL; adjustment ±21 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 30 publications
4
67
0
5
Order By: Relevance
“…Overall, the safety profile of insulin icodec was comparable to that of once-daily insulin glargine U100 in all three of the phase 2 studies reported (Table 3) [75][76][77], with only one event of severe hypoglycemia with cognitive impairment requiring external assistance for recovery (level 3) reported across these trials [75]. The incidences of combined clinically significant (level 2, defined as a blood glucose value <54 mg/dL) or severe (level 3) hypoglycemia were low overall (16% for insulin icodec vs. 9.8% for insulin glargine U100 in the 26week trial [75]), and were not statistically different between insulin icodec and insulin glargine U100 [75][76][77]. Furthermore, the event rate was very low over 26 weeks in insulin-naive patients for both insulin icodec and insulin glargine U100 (0.53 events/patient/year and 0.46 events/patient/year, respectively [75]).…”
Section: Insulin Icodecmentioning
confidence: 85%
See 3 more Smart Citations
“…Overall, the safety profile of insulin icodec was comparable to that of once-daily insulin glargine U100 in all three of the phase 2 studies reported (Table 3) [75][76][77], with only one event of severe hypoglycemia with cognitive impairment requiring external assistance for recovery (level 3) reported across these trials [75]. The incidences of combined clinically significant (level 2, defined as a blood glucose value <54 mg/dL) or severe (level 3) hypoglycemia were low overall (16% for insulin icodec vs. 9.8% for insulin glargine U100 in the 26week trial [75]), and were not statistically different between insulin icodec and insulin glargine U100 [75][76][77]. Furthermore, the event rate was very low over 26 weeks in insulin-naive patients for both insulin icodec and insulin glargine U100 (0.53 events/patient/year and 0.46 events/patient/year, respectively [75]).…”
Section: Insulin Icodecmentioning
confidence: 85%
“…Once-weekly insulin for T2D without previous insulin treatment a [75] Insulin-naive patients treated with oral glucose-lowering drugs [76] Patients switching from daily basal insulin with one or more oral glucose-lowering drugs [77] Insulin of hypoglycemic events with blood glucose <54 mg/dL (<3.0 mmol/L) (Table 2). Analysis of continuous glucose monitoring (CGM) data showed that, at week 32, the relative risk of hypoglycemia (blood glucose ≤70 mg/dL [≤3.9 mmol/L]) with BIF-A1 compared with insulin degludec was 0.70 (90% confidence interval [CI] 0.51 to 0.95) and 0.55 (95% CI 0.41 to 0.73) for 24 h and nocturnal measures, respectively [74].…”
Section: Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…In a third study, several icodec titration algorithms were tested in insulin-naïve patients with T2D [14]. Unsurprisingly, an algorithm with a lower target fasting plasma glucose (FPG) target (3.9-6.0 mmol/l vs. 4.4-7.2 mmol/l with the other algorithms) resulted in better HbA1c-levels, but also in considerably higher rates of hypoglycaemia.…”
Section: Clinical Data Of Once-weekly Insulinsmentioning
confidence: 99%